Perjanjian Sewa Menyewa Tenant Bidang Usaha Makanan Dengan PT Angkasa Pura Aviasi Berdasarkan Landasan Syariat Islam - Nurhalimah Tusadiah Siregar; Andri Soemitra (Lembaga Pengembangan Kinerja Dosen, 2025)
This research aims to analyze the legal aspects of the tenant lease agreement in the food business sector with PT Angkasa Pura Aviation based on the principles of Islamic law. This research uses descriptive qualitative method with data collection techniques through literature review, in-depth interviews, and participatory observation. The results showed that the lease agreement applied has referred to the principles of justice, legal certainty, and expediency as proposed by Gustav Radbruch's legal theory. In the perspective of Islamic law, this agreement fulfills the pillars and conditions of the ijarah contract, which include clarity of the rental object, agreement between the contracting parties, and transparent price and rental period provisions. However, some challenges are still found in its implementation, such as delays in rental payments by business partners and the need for a dispute resolution mechanism that is more in line with Islamic principles. Therefore, it is necessary to optimize the implementation of the lease contract so that it is more in line with sharia values and equitable business principles.